Evaluating "The REST of Your Life, " a Workplace Health Program to Improve Employee Sleep, Health, Energy, and Productivity. Issue 5 (June 2022) - Robbins, Rebecca; Yi, Fanchao; Chobotar, Todd; Hawkins, Sarah; Putt, Denise; Pepe, Julie; Manoucheri, Manoucher
Purpose: Sleep is critical for employee health, well-being, and productivity. Our purpose is to evaluate a sleep-focused interactive workplace health promotion program. Design: We evaluate sleep and mental health before and after exposure to the program using a pre/post quasi-experimental pilot study design with surveys administered at baseline and 1-, 6-, and 12 months post-exposure (Phase 1). We design program evaluation surveys for dissemination when the program is offered broadly to hospital employees (Phase 2). Setting: The study was conducted at a large teaching hospital in the Southeast U.S. in 2016. Subjects: Subjects were full-time hospital employees. Intervention: The program was presented to subjects in one four-hour interactive session. Measures: In Phase 1 (n = 55), surveys included the validated Apnea Risk Evaluation System, Dysfunctional Beliefs About Sleep, Generalized Anxiety Disorder-7, Pittsburgh Sleep Quality Index and Patient Health Questionnaire. Phase 2 (n = 3935) utilized program evaluation surveys. Analysis: We compare survey responses between pre- and post-program using a repeated measures analysis of variance with post-hoc tests. Results: Statistically significant improvement in all sleep and mental health domains was demonstrated. In Phase 2, 81.9% reported "strongly agree" to willingness to recommend the program to co-workers. Conclusion: We demonstrate improvement in employee sleep and mental health after exposure to a novel workplace health promotion program to improve sleep.